Questioning the Notion of Financial Gain as the Primary Motivation of Human Traffickers - Clarke, Matthew (Anti-Trafficking Review, 2022)
One common belief in the anti-trafficking field is that the primary motivation of traffickers is financial gain. This short paper describes recent examples of that belief among researchers and practitioners and suggests that it is not warranted by the available evidence. My intention is to stimulate conversation and to call for improved documentation and analysis of perpetrator motivations. I encourage a more nuanced appreciation of those motivations by policymakers and the larger anti-trafficking community.